2020
DOI: 10.1016/j.jebo.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous monitoring and remote work

Abstract: Credible monitoring of remote workers presents unique challenges that may reduce the benefits of formal organization for their management. We consider whether increasing the salience of monitor productivity without changing incentive contracts or monitoring technology leads to changes in remote worker performance. Results from a field experiment run among multidimensional task workers in Kenya demonstrate that increasing the visibility of monitor activity improves performance on task dimensions not being direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The availability of software programs that track employee tasks in the remote work environment has increased the ability of managers to monitor work activity more accurately. In their study, Jensen et al (2020) found that even when direct employee outputs are difficult to measure, managers may be able to improve productivity in the remote work environment by providing quality and frequent feedback regarding performance. This feedback increases worker autonomy and decreases disruptions in the work environment which ultimately improves job satisfaction.…”
Section: Environmental Influencesmentioning
confidence: 99%
“…The availability of software programs that track employee tasks in the remote work environment has increased the ability of managers to monitor work activity more accurately. In their study, Jensen et al (2020) found that even when direct employee outputs are difficult to measure, managers may be able to improve productivity in the remote work environment by providing quality and frequent feedback regarding performance. This feedback increases worker autonomy and decreases disruptions in the work environment which ultimately improves job satisfaction.…”
Section: Environmental Influencesmentioning
confidence: 99%
“…Only Tsareva and Yu (2020) and Manokha (2020) included specific technological platforms for employee monitoring. Jensen et al (2020) provided a direct field study of remote work and workflow, the only study of its kind located. There was…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action here is as follows: employees know that their results are valued and considered, their satisfaction with work and, as a result, productivity increases. No impact of monitoring without feedback on labor productivity was found [19].…”
Section: Organizational-managerial Effectsmentioning
confidence: 97%